2012
DOI: 10.5551/jat.8326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Coronary Artery Disease and Non-HDL-C, and Effect of Highly Purified EPA on the Risk of Coronary Artery Disease in Hypercholesterolemic Patients Treated with Statins: Sub-Analysis of the Japan EPA Lipid Intervention Study (JELIS)

Abstract: Aim:The present study examined the importance of reducing non-high-density lipoprotein cholesterol (non-HDL-C) for the primary prevention of the occurrence of coronary artery disease (CAD) in the JELIS, and the effects of EPA. Methods: The patients were distributed into 4 subgroups using the lipid management goal for LDL-C recommended by the Japan Atherosclerosis Society guideline (2007) and the goal for non-HDL-C defined as 30 mg/dL higher than LDL-C: A) achieved both goals; B) achieved the LDL-C but not non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 42 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…216 Several nonstatins also have RCT evidence for ASCVD reduction as statin adjuncts in subgroup analyses of patients with elevated triglycerides or elevated triglycerides plus low HDL-C concentrations. 198 These include eicosapentaenoic acid ethyl esters, 313,326 fibrates (Fig. 14), 314,327 and niacin.…”
Section: Combination Drug Therapymentioning
confidence: 99%
“…216 Several nonstatins also have RCT evidence for ASCVD reduction as statin adjuncts in subgroup analyses of patients with elevated triglycerides or elevated triglycerides plus low HDL-C concentrations. 198 These include eicosapentaenoic acid ethyl esters, 313,326 fibrates (Fig. 14), 314,327 and niacin.…”
Section: Combination Drug Therapymentioning
confidence: 99%
“…non HDL-C level of ≥ 190 mg/dL. In a subanalysis of the JELIS that compared the groups that achieved both LDL-C and non HDL-C management goals, the other groups exhibited higher incidences of CAD 53) . Recently, it was demonstrated that the non HDL-C level in Japanese individuals is equal to LDL-C +30 mg/dL, the same as that observed in the U.S 54,55) .…”
Section: )mentioning
confidence: 99%
“…These results are consistent with those from the 5 other cardiovascular outcome trials that evaluated the benefits of a triglyceride-lowering therapy in the subgroup of patients with significant hypertriglyceridemia. [6][7][8][9][10] The measurement of carotid intima-media thickness (cIMT) is a well-validated surrogate end point for evaluating the impact of a therapy on cardiovascular risk. 11,12 cIMT has been shown to correlate with risk of future cardiovascular events, 11,12 and changes in cIMT over time have been used extensively to evaluate the potential clinical efficacy of antiatherosclerotic agents.…”
mentioning
confidence: 99%